2019
DOI: 10.1002/1873-3468.13581
|View full text |Cite
|
Sign up to set email alerts
|

Methylosome protein 50 associates with the purinergic receptor P2X5 and is involved in osteoclast maturation

Abstract: Purinergic signaling plays important roles in bone. P2X5, a member of ligandgated ion channel receptors, has been demonstrated to regulate osteoclast maturation. However, the molecular mechanism of P2X5-mediated osteoclast regulation remains unclear. Here, we identified methylosome protein 50 (MEP50), a critical cofactor of the protein arginine methyltransferase 5 (PRMT5), as a P2X5-associating molecule. RNAi-mediated knockdown of MEP50 results in decreased formation of mature osteoclasts. MEP50 associates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Then, BamHI-XhoI fragment of the mouse Pcdh7ΔSET was cut out from the vector and subcloned into the BamHI-XhoI fragment of the pMX-Flag vector to generate the pMX-Pcdh7ΔSET vector. Mouse Pcdh7 intracellular region (iPcdh7) and ΔSET intracellular region (iPcdh7ΔSET) were amplified with the following primers: sense primers with the SalI site (5′-TTTGTCGACTGCAGGT CCAAAAATAA AAATGGC-3′ for iPcdh7, and 5′-TTTGTCGACTCAGACAGCCCAAGCATGGGCCGA-3′ for iPcdh7ΔSET) and an antisense primer with the XhoI site (5′-TTTCTCGAGCAGATAAACTTCTCTTCTAGTGAG-3′) and cloned into the XhoI fragment of the pMX-hCD3-Flag vector [ 44 ] to generate pMX-hCD3-iPcdh7 vector and pMX-hCD3-iPcdh7ΔSET vector.…”
Section: Methodsmentioning
confidence: 99%
“…Then, BamHI-XhoI fragment of the mouse Pcdh7ΔSET was cut out from the vector and subcloned into the BamHI-XhoI fragment of the pMX-Flag vector to generate the pMX-Pcdh7ΔSET vector. Mouse Pcdh7 intracellular region (iPcdh7) and ΔSET intracellular region (iPcdh7ΔSET) were amplified with the following primers: sense primers with the SalI site (5′-TTTGTCGACTGCAGGT CCAAAAATAA AAATGGC-3′ for iPcdh7, and 5′-TTTGTCGACTCAGACAGCCCAAGCATGGGCCGA-3′ for iPcdh7ΔSET) and an antisense primer with the XhoI site (5′-TTTCTCGAGCAGATAAACTTCTCTTCTAGTGAG-3′) and cloned into the XhoI fragment of the pMX-hCD3-Flag vector [ 44 ] to generate pMX-hCD3-iPcdh7 vector and pMX-hCD3-iPcdh7ΔSET vector.…”
Section: Methodsmentioning
confidence: 99%
“…A series of studies has recently reported that another P2X receptor, P2X5, is required for osteoclast multinucleation [ 174 , 175 , 176 ]. Kim et al found that P2X5 is highly expressed during the fusion phase of multinucleated osteoclasts and multinucleated giant cells, and that blocking P2X5 signaling with an antagonist or ATP diphosphatase apyrase inhibits multinucleation and resorptive ability but not osteoclast differentiation.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…However, it has been shown that murine P2X5 is highly expressed during the maturation phase of bone-resorbing osteoclasts (OCs) and that P2X5 gene deletion ( mP2 × r5 −/− ) diminishes OC maturation in vitro, and also decreases the rate bone loss in inflamed parietal calvarium (skull) in vivo, yet without affecting normal bone development [ 62 ]. The process of murine P2X5-dependent OC maturation involves methylosome protein 50 which physically associates with the C-terminus of the P2X5 receptor [ 63 ]. Accordingly, mutant mP2X5 subunits with the TM2 domain and C-terminus deleted (mP2X5Δ268) also results in impaired OC maturation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The process of murine P2X5-dependent OC maturation involves methylosome protein 50 which physically associates with the C-terminus of the P2X5 receptor [ 63 ]. Accordingly, mutant mP2X5 subunits with the TM2 domain and C-terminus deleted (mP2X5Δ268) also results in impaired OC maturation [ 63 ]. Expression levels of IL1β, IL6, IL17α, and TNF-sf11 were significantly lower in P2 × r5 −/− mice compared to WT mice, and this reduction led to decreased periodontitis (gum disease) and decreased alveolar bone loss compared with WT mice, when challenged by LPS from Porphyromonas gingivalis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%